2012
DOI: 10.4103/1947-2714.95904
|View full text |Cite
|
Sign up to set email alerts
|

HIV-Tuberculosis: A Study of Chest X-Ray Patterns in Relation to CD4 Count

Abstract: Background:Fight against human immunodeficiency virus (HIV) is incomplete without addressing problems associated with difficult diagnosis of tuberculosis in HIV-Tuberculosis coinfected patients. Chest X-ray is a primary tool to evaluate tuberculosis in HIV.Aim:To assess and compare various radiological patterns of pulmonary tuberculosis in HIV patients and compare these patterns in relation to CD4 counts.Materials and Methods:Prospective cohort study was conducted in a tertiary hospital in South India from Sep… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
43
2
3

Year Published

2013
2013
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 52 publications
(59 citation statements)
references
References 4 publications
(5 reference statements)
5
43
2
3
Order By: Relevance
“…Similarly a study done by Padyana et al .,[12] at a tertiary care hospital of South India, among 200 HIV positive patients, showed that 54 (27%) patients had HIV/TB co-infection and remaining 146 (73%) were HIV positive alone. Another study done by Kebede and Wabe[13] in South West Ethiopia, among 296 patients on concomitant tuberculosis and antiretroviral therapy at hospital treatment center, of them only 24 (8.1%) were co-infected by HIV and TB.…”
Section: Discussionmentioning
confidence: 62%
“…Similarly a study done by Padyana et al .,[12] at a tertiary care hospital of South India, among 200 HIV positive patients, showed that 54 (27%) patients had HIV/TB co-infection and remaining 146 (73%) were HIV positive alone. Another study done by Kebede and Wabe[13] in South West Ethiopia, among 296 patients on concomitant tuberculosis and antiretroviral therapy at hospital treatment center, of them only 24 (8.1%) were co-infected by HIV and TB.…”
Section: Discussionmentioning
confidence: 62%
“…The present study at Al-Ameen Medical college Hospital at Bijapur, Southern India, shows 16.66% prevalence of tuberculosis infection among HIV positive patients, which is lower compared to other south Indian studies done by Padyana et al and Shrivastava et al Padyana et al [18] at a tertiary care hospital of South India, among 200 HIV positive patients, showed that 54 (27%) patients had HIV/TB co-infection. Shrivastava et al [19] demonstrated a prevalence of 20% among 305 HIVseropositive patients referred from Integrated Counselling and Treatment Center to TB clinic of Southern India.…”
Section: Graph 1: Tb Status Among Hiv Positive Patientscontrasting
confidence: 44%
“…[1234] TB of the spine is one of the oldest demonstrated diseases of mankind and is the common extrapulmonary form of TB. The morbidity and mortality rate due to spinal TB is higher than other infections in developing countries with dense population.…”
Section: Introductionmentioning
confidence: 99%